SmartPLS 4 for Smart Facilitators: Optimizing PLS-SEM Analysis in TKMP Program - Lestari Agusalim (GUYUB: Journal of Community Engagement, 2025)
Community Service through PLS-SEM Training with SmartPLS 4 aims to enhance the analytical skills of facilitators in the Beginner Independent Workforce Program. This program is designed to strengthen the entrepreneurial capacity of beginner entrepreneurs in Indonesia, focusing on the development of micro and small businesses through comprehensive training in business planning, marketing, financial management, and product development. The training method used is participatory and practical, incorporating a real-project simulation with a focus on field data collected by participants, who are facilitators. This method encourages active engagement, allowing facilitators to directly apply their own data in PLS-SEM analysis to understand relationships between variables influencing business success. This method provides a solid foundation for making more data-driven, informed decisions. The participatory approach used in the training allows facilitators to be directly involved in the mentoring process, helping beginner entrepreneurs with relevant and effective solutions. The training results show a significant improvement in facilitators' analytical skills, with an average pre-test score of 53 and a post-test score of 89.5. The Wilcoxon Signed-Rank test confirms a significant difference, indicating the training's effectiveness in enhancing the quality and effectiveness of mentoring. Additionally, facilitators are able to provide better insights into market potential and guide beginner entrepreneurs in facing market challenges.